Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1055/s-0028-1087188
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Effects of Eplerenone and Spironolactone on Adrenal Cell Steroidogenesis

Abstract: Summary Spironolactone and eplerenone are widely used as mineralocorticoid antagonists. Spironolactone has several nonspecific actions including inhibition of androgen receptor and steroid hormone biosynthesis. While studies have shown that eplerenone does not exhibit nonspecific actions on androgen receptor, its effects on steroid hormone production have not been reported. Herein, the effects of eplerenone (0.1 to 30 µM) and spironolactone (0.1 to 30 µM) on steroid production were examined in human adrenocort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 50 publications
(44 reference statements)
0
16
0
Order By: Relevance
“…The lower plasma aldosterone may then lead to less uptake of aldosterone into the hypothalamus, resulting in lower hypothalamic content. Alternatively, independent of the MR, as one of its nonspecific actions, spironolactone may directly inhibit enzymes involved in steroid biosynthesis (32), thereby preventing increases in hypothalamic aldosterone by high salt intake.…”
Section: Discussionmentioning
confidence: 99%
“…The lower plasma aldosterone may then lead to less uptake of aldosterone into the hypothalamus, resulting in lower hypothalamic content. Alternatively, independent of the MR, as one of its nonspecific actions, spironolactone may directly inhibit enzymes involved in steroid biosynthesis (32), thereby preventing increases in hypothalamic aldosterone by high salt intake.…”
Section: Discussionmentioning
confidence: 99%
“…Racial difference in response to MR blockade may exist: African Americans with heart failure are less responsive to the renal effect of spironolactone and develop less hyperkaliemia (Cavallari et al, 2004); this is not the case with eplerenone (Flack et al, 2003). It has been reported that spironolactone (at micromolar concentrations) inhibits aldosterone biosynthesis (Netchitailo et al, 1985) and blocks enzymes involved in steroidogenesis (Penhoat et al, 1988;Ye et al, 2009). In contrast, eplerenone (1-30 mM) did not impair basal and angiotensin II-induced cortisol and aldosterone production in human adrenocortical H295R cells (Ye et al, 2009).…”
Section: A Steroidal Compoundsmentioning
confidence: 99%
“…It has been reported that spironolactone (at micromolar concentrations) inhibits aldosterone biosynthesis (Netchitailo et al, 1985) and blocks enzymes involved in steroidogenesis (Penhoat et al, 1988;Ye et al, 2009). In contrast, eplerenone (1-30 mM) did not impair basal and angiotensin II-induced cortisol and aldosterone production in human adrenocortical H295R cells (Ye et al, 2009). Thus spironolactone and eplerenone have differential effects on steroidogenesis.…”
Section: A Steroidal Compoundsmentioning
confidence: 99%
“…This antiandrogen effect has been used to benefit in the treatment of hirsutism6 and acne 7. Spironolactone has also been shown to inhibit cytochrome P450 which is necessary for the synthesis of androgens in the adrenal glands and testis8 and reduces the production of cortisol and aldosterone 9…”
Section: Introductionmentioning
confidence: 99%